41, 39. 37A and 37 Charles Street, January 14, 1973 - Waid, C. Franklin (Tufts Archival Research Center, 2005)
Street-level view northeast of (left to right) 41, 39. 37A and 37 Charles Street, located between Chestnut Street to the south and Mount Vernon Street to the north. Signage adorns the facades of the buildings, which face west towards Charles Street. A street lamp and parking meters line the sidewalk in front of the buildings. Two people stand beside several stacks of newspapers in front of one of the buildings. Commercial products are displayed in the storefront windows of both 37A and 39 Charles Street. 7 3/8 x 9 3/8, 7 7/8 x 9 7/8 overall Photographs